The Performance of Modern PLS and Conventional SEM for Second Order Construct of Family Communication Pattern Model - AFTHANORHAN, ASYRAF; BAKAR, AZIYAH ABU; AIMRAN, NAZIM; RASHID, NORFADZILAH (The journal of contemporary issues in business and government, 2021)
This paper is aims to determine the performance of modern Partial Least Square (PLS) and Conventional SEM in family research. As such, the adoption of Measurement of Family Communication became the subject for testing their effectiveness. Measurement of Family Communication Pattern is broadly used to assess the happiness of the family either happy or unhappy and it was frequently noted as one of the confirmatory research. It shows that the conventional SEM was better than modern PLS in the presence of the second-order construct.